2017
DOI: 10.2989/00306525.2017.1388300
|View full text |Cite
|
Sign up to set email alerts
|

Managing human disturbance: factors influencing flight-initiation distance of birds in a West African nature reserve

Abstract: Dear Miss Braimoh: Ref: Managing human disturbance: factors influencing flight initiation distance of birds in a West African nature reserve Our referees have now considered your paper and have recommended publication in Ostrich. We are pleased to accept your paper, but reserve the right to suggest further changes and implement minor edits upon agreement with yourselves. We will then forward all documents to the publisher for copy editing and typesetting. You will receive proofs for checking, and instructions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 78 publications
4
14
0
Order By: Relevance
“…We also found species-specific FID and FR, which corroborated with other studies (Burger & Gochfeld 1998;Blumstein et al 2003;Braimoh et al 2018). Previous studies demonstrated species-specific responses that are driven by several factors such as previous exposure to humans (Sproat et al 2020), individual experiences (Martín & López 2015), hunting pressure (Stankowich 2008;Sproat et al 2020) and life history strategies (Bennett & Owens 2002).…”
Section: Discussionsupporting
confidence: 91%
“…We also found species-specific FID and FR, which corroborated with other studies (Burger & Gochfeld 1998;Blumstein et al 2003;Braimoh et al 2018). Previous studies demonstrated species-specific responses that are driven by several factors such as previous exposure to humans (Sproat et al 2020), individual experiences (Martín & López 2015), hunting pressure (Stankowich 2008;Sproat et al 2020) and life history strategies (Bennett & Owens 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Lateralization of vigilance can differ even between closely related species, as shown, for example, in the three species of emberizid sparrows (Franklin and Lima, 2001). In some species, vigilance behaviour evokes a right-eye bias (Franklin and Lima, 2001;Chivers et al, 2016;Romano et al, 2017) or no bias at all (Franklin and Lima, 2001;Beauchamp, 2013;Blumstein et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The most consistent difference seen in foraging behaviour and body mass and body condition was between HHP and LHP days. Coping with short-term temporal fluctuations in resource availability, which might also correlate with anthropogenic disturbance (Braimoh et al 2018) and predation patterns (i.e. fewer predators on campus when human foot traffic is high) require a high level of adaptability.…”
Section: Discussionmentioning
confidence: 99%